2020
DOI: 10.1126/science.abe1107
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting and de novo humoral immunity to SARS-CoV-2 in humans

Abstract: Zoonotic introduction of novel coronaviruses may encounter preexisting immunity in humans. Using diverse assays for antibodies recognizing SARS-CoV-2 proteins, we detect preexisting humoral immunity. SARS-CoV-2 spike glycoprotein (S)-reactive antibodies were detectable by a flow cytometry-based method in SARS-CoV-2-uninfected individuals and were particularly prevalent in children and adolescents. They were predominantly of the IgG class and targeted the S2 subunit. By contrast, SARS-CoV-2 infection induced hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

83
991
8
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 823 publications
(1,096 citation statements)
references
References 45 publications
83
991
8
14
Order By: Relevance
“…2 and Supplementary Tables 1-3). Overall seroconversion rates of 88% were similar to the general population [4,6,7] and higher than that reported by Table 1 Demographics, patient and disease characteristics, treatment and outcomes in patients with acute leukemia and COVID-19. This patient subsequently tested positive one day after initial negative (for four days) again 21 days after second negative test (for eight days) ( Supplementary Fig.…”
Section: To the Editorsupporting
confidence: 56%
See 2 more Smart Citations
“…2 and Supplementary Tables 1-3). Overall seroconversion rates of 88% were similar to the general population [4,6,7] and higher than that reported by Table 1 Demographics, patient and disease characteristics, treatment and outcomes in patients with acute leukemia and COVID-19. This patient subsequently tested positive one day after initial negative (for four days) again 21 days after second negative test (for eight days) ( Supplementary Fig.…”
Section: To the Editorsupporting
confidence: 56%
“…Serum samples were taken a median of 9.5 days after positive PCR test for SARS-CoV-2 (range 1-25 days) and subsequent longitudinal serum samples taken between 2 and 103 days post onset of symptoms (POS). These were screened for anti-SARS-CoV-2 antibodies using ELISA to the external Spike glycoprotein (S1 subunit) and internal Nucleoprotein (N) [4][5][6]. Total serum IgG was within in the normal range in each case, excluding hypogammaglobinaemia.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Age has been shown to be the biggest risk factor for more severe disease and death due to (17). In Supplemental Figure 3 A, we demonstrate that S2-IgG antibodies are present in patients as early as the day of symptom onset, suggesting that these antibodies may be boosted from a previous coronavirus infection.…”
Section: Discussionmentioning
confidence: 66%
“…Of note, Ng et al (Science, 2020) have identified several epitopes that were recognized with cross-reactive antibodies by uninfected patients proving the presence of preexisting antibodies recognizing SARS-CoV-2 [28]. These results considering also the finding of preexisting T cell memory against seasonal HCoVs and SARS-CoV-2 (21) may shed light on the SARS-CoV-2 natural infection having in mind that this protective cross immunity does not last for long time and probably is not sterilizing as well.…”
Section: Discussionmentioning
confidence: 99%